Research in the Physician's Office: Navigating the Ethical Minefield - Snyder, Lois (The Hastings Center report, 2008)
Dr. Smith is an internist in private practice who works at an inner city clinic affiliated with a university hospital. He is also a member of the university faculty. Many of Dr. Smith's patients have type 2 diabetes mellitus and struggle with health care and other costs. Thinking about opportunities to better serve his patients and advance his career, Dr. Smith considers conducting clinical research in his office. ACME is a respected pharmaceutical company that for decades has engaged in research, development, and production of widely used drugs. Several of ACME's oral agents for type 2 diabetes will soon go off patent. In an effort to retain its market share in this class of drugs, ACME wants to complete clinical trials expeditiously and obtain approval for its new oral hypoglycemic medicine. The company approaches Dr. Smith to be a coinvestigator in its multicenter clinical trial.